INVESTIGATION OF FLIP-FLOP PERFORMANCE ON DIFFERENT TYPE AND ARCHITECTURE IN SHIFT REGISTER WITH PARALLEL LOAD APPLICATIONS - Dwi Purnomo; Machmud Roby Alhamidi; Ari Wibisono; Muhammad Iqbal Tawakal (Faculty of Computer Science - Universitas Indonesia, 2015)
Register is one of the computer components that have a key role in computer organisation. Every computer contains millions of registers that are manifested by flip-flop. This research focuses on the investigation of flip-flop performance based on its type (D, T, S-R, and J-K) and architecture (structural, behavioural, and hybrid). Each type of flip-flop on each architecture would be tested in different bit of shift register with parallel load applications. The experiment criteria that will be assessed are power consumption, resources required, memory required, latency, and efficiency. Based on the experiment, it could be shown that D flip-flop and hybrid architecture showed the best performance in required memory, latency, power consumption, and efficiency. In addition, the experiment results showed that the greater the register number, the less efficient the system would be.